Diabetes distress in Barbadian adults with type 2 diabetes - Allison DaSantos; Carlisle Goddard; Dalip Ragoobirsingh (AIMS Press, 2022)
Purpose: Psychological disorders such as diabetes distress may negatively influence how patients effectively manage their illness. Therefore, discernment of such influential psychosocial components could be pertinent in promoting competent diabetes management. The vital psychosocial aspect of diabetes distress in diabetes management within the Caribbean context remains unexplored. The purpose of this study therefore was to investigate the prevalence and distribution of diabetes distress (DD), and explore its relationship to socio-demographic and clinical characteristics in Barbadian adults with type 2 diabetes(T2DM). Methods: A cross-sectional survey was conducted with adults (n = 509) ages 20-80 years with T2DM. The survey comprised, a profile section, and a standardized questionnaire-the Diabetes Distress Scale (DDS). In addition, biological (A1C and blood pressure measurements were also collected. Results: The sample comprised 30.8% males and 69.2% females. Moderate to high DD identified in 17% of the patients (9.4% moderate distress, 7.2% high distress). Moderate distress was more frequent in unmarried persons; younger persons had high DD. There was no difference in rates of moderate to high DD in women (16.7%) compared to men (16.2%) and, as age and years lived with diabetes increased, diabetes distress decreased. Conclusions: The results emphasized the need for considerations that must be given to Barbadian diabetes patients' mental well-being. In recognition of the role DD plays in the patients' experiences, screening should be incorporated into clinical care.